GO.DB. architects. A Different Approach to Architectural Practice in 1970s Valencia - Palomares Figueres, Maite; Usó Martín, Fernando (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
This research analyzes the organizational structure of GO.DB. arquitectos, firm founded by architects Fernando Martínez García-Ordoñez (GO) and Juan María Dexeus Beatty (DB). Their strategy was conceived to approach architectural practice from a business-oriented perspective, as a response to the increasing complexity of the technical design process. García-Ordoñez’s involvement in the Technical Office of the Plan Sur allowed him to establish connections with engineers and large-scale infrastructure projects, an influence that was further enriched by his exposure to the collaborative and multidisciplinary work dynamics characteristic of major American firms. These references resonated with the religious beliefs García-Ordoñez shared with Miguel Fisac, with whom he collaborated at the beginning of his career, awakening his interest in industrialized construction and experimentation. As a result, GO.DB. arquitectos developed a distinctive multidisciplinary organizational model, characterized by a tendency towards specialization and departmentalization, which contributed to the firm’s expansion and diversification.
Keywords: GO.DB architects; corporate structure; departmentalisation; multidisciplinary; macro-study; Modern Movement